2009
DOI: 10.12973/ejmste/75278
|View full text |Cite
|
Sign up to set email alerts
|

Socially Response-able Mathematics Education: Implications of an Ethical Approach

Abstract: This paper discusses an approach to mathematics education based on the concept of ethical responsibility. It argues that an ethical approach to mathematics teaching lays the theoretical foundations for social justice concerns in the discipline. The paper develops a particular understanding of ethical responsibility based on the writings of Emanuel Levinas and discusses its implication for decision making on the curriculum and pedagogy in mathematics education. The paper argues that such an approach is consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 23 publications
1
47
0
1
Order By: Relevance
“…Investigations of social justice within mathematics education have focussed on the learnerteacher relationship and the pedagogical practices used in mathematics classrooms (Atweh & Brady, 2009). However, Fairclough's (2003) description of learning suggests that as one part of the entangled relationships that contributes to learning, pedagogical practices, as social practices, involve the valuing by participants of certain systems of knowledge.…”
Section: Situating Pedagogical Approaches As An Issue Of Social Justicementioning
confidence: 99%
“…Investigations of social justice within mathematics education have focussed on the learnerteacher relationship and the pedagogical practices used in mathematics classrooms (Atweh & Brady, 2009). However, Fairclough's (2003) description of learning suggests that as one part of the entangled relationships that contributes to learning, pedagogical practices, as social practices, involve the valuing by participants of certain systems of knowledge.…”
Section: Situating Pedagogical Approaches As An Issue Of Social Justicementioning
confidence: 99%
“…The Productive Pedagogies framework does not, however, provide a ready-made technique for teaching but, rather, an approach to creating a place, space and vocabulary for teachers to use in classroom instruction discourse [46]. Therefore, in its implementation in the classroom, teachers are required to adapt the dimensions of the framework to be more in line with the 'local' situation.…”
Section: Productive Pedagogies Frameworkmentioning
confidence: 99%
“…They concluded that "ability and attitude work in tandem to explain mathematical success" (p. 702). According to Atweh and Brady (2009) students are more likely to continue to study mathematics and put greater effort in learning mathematics if their perceived value of mathematics is relevant to their life and future carriers. Hannula (2012) further identified that values are part of the motivational dimension.…”
Section: Attitudes and Achievementmentioning
confidence: 99%